A historical approach to the ventricular system of the brain (2017)
Introduction: The ventricular system of the brain was first described, partially, in the third century BC. Since then, several researchers have contributed to better understand this system, unraveling its position in the central nervous system, and relating it with certain functional aspects following philosophical concepts that have allowed a clearer approach to cavitations regarding the formation of the cerebrospinal fluid.Objective: To describe the most relevant concepts of the history of the ventricular encephalic system of the brain.Materials and methods: Various literature sources related to the ventricular system were consulted, and then chronologically organized, so that a more concrete approximation of the functional morphology of the ventricular system could be provided.Conclusion: Aristotle was the first to approach the ventricular system of the brain. Over time, his knowledge on the organization, function and number of cavities was debugged to the point of proposing the existence of eight ventricles. Today, five ventricles are recognized, four of which are encephalic components: two in the brain, one in the diencephalon, other in the brainstem, and a fifth in the terminal part of the spinal cord.